Improvement of clay slurry for land reclamation - Wu, Dongqing. (2009)
Stabilization is required when clay slurry is used for land reclamation. Preloading, often in combination with vertical drains, is generally recognized as one of the most reliable methods to improve very soft clays. However the classical consolidation theory cannot be used to calculate the time required for the consolidation because of the large deformations and the change of the compressibility and permeability during the consolidation process.